Improving Indonesian Speaking Skills By Using The Role-Playing Method - Yuyun Bahtiar; Maskhurin Fajarina; Ni Made Laksmi Dewi Kristiani; Iin Baroroh Ma’arif (Universitas Muhammadiyah Gresik, 2024)
This research aims to improve speaking skills through the role-playing method for fifth-grade students at SD Negeri 5 Tonja Denpasar. This type of research is Classroom Action Research. The object of the research is speaking skills. The data collection methods used are observation, tests, and documentation. The data analysis techniques used are qualitative descriptive and quantitative descriptive. Learning actions in cycle I students play roles based on conversation scripts. Students do not experience problems in linguistic aspects (vocabulary/phrases and sentence structures used) and non-linguistic aspects (courage, friendliness, and attitude). Cycle II role-playing actions based on drama scripts. Cycle II focuses more on linguistic aspects (stress, pronunciation, and tone and rhythm) and non-linguistic aspects (fluency and mastery of the material) which are still lacking. Learning speaking skills through role-play methods based on drama scripts shows an increase in students' speaking skills. Improvement is shown by the results of students' speaking skill scores. The improvements that occurred were, (1) the average student pre-action score was 57.3 with a completion percentage of 23.08%, (2) the average cycle I evaluation score was 76.92 with a completion percentage of 53.85%, (3) the average evaluation score for cycle II was 83.46 with a completion percentage of 84.61%.